The potential of high-rate GPS for strong ground motion assessment - Michel, Clotaire; Kelevitz, Krisztina; Houlié, Nicolas; Edwards, Brent; Psimoulis, Panos; Su, Zhenzhong; Clinton, John; Giardini, Domenico (Seismological Society of America, 2017)
We show that high-rate GPS can have a vital role to play in near real-time monitoring of potentially destructive earthquakes. We do this by investigating the potential of GPS in recording strong ground motions from earthquakes in Switzerland and Japan. The study uses finite-fault stochastic ground motion simulation based on Fourier amplitude spectra and duration models previously developed for both countries, allowing comparisons in terms of both Fourier and time domain characteristics (here the Peak Ground Velocity, PGV). We find that earthquakes of magnitude Mw>5.8 can be expected to be recorded by GPS in real-time at 10 km distance, i.e. their Fourier spectrum exceeds the noise of the instruments enough to be used in strong motion seismology. Post-processing of GPS time series lowers the noise and can improve the minimum observable magnitude by 0.1-0.2. As GPS receivers can record at higher rates (> 10 sps), we investigate which sampling rate is sufficient to optimally record earthquake signals and conclude that a minimum sampling rate of 5 sps is recommended. This is driven by recording events at short distances (below 10 km for magnitude 6 events and below 30 km for magnitude 7 events). Furthermore, the Maximum Ground Velocity derived from GPS is compared to the actual PGV for synthetic signals from the stochastic simulations and the 2008 Mw=6.9 Iwate earthquake. The proposed model, confirmed by synthetic and empirical data, shows that a reliable estimate of PGV for events of about magnitude 7 and greater can be basically retrieved by GPS in real-time and could be included for instance in ShakeMaps for aiding post-event disaster management.